2022
DOI: 10.1002/2211-5463.13438
|View full text |Cite
|
Sign up to set email alerts
|

ARL2 is required for homologous recombination repair and colon cancer stem cell survival

Abstract: ARL2 regulates the dynamics of cytological components and is highly expressed in colon cancer tissues. Here, we report novel roles of ARL2 in the cell nucleus and colon cancer stem cells (CSCs). ARL2 is expressed at relatively low levels in K‐RAS active colon cancer cells, but its expression is induced in CSCs. Depletion of ARL2 results in M phase arrest exclusively in non‐CSC cultured cells; in addition, DNA break stress accumulates in CSCs leading to apoptosis. ARL2 expression is positively associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…In addition, the CSC preference for HRR has also been suggested in breast and gastric CSCs [43,44]. We also recently suggested that HRR may be indispensable for colon CSC survival [45]. The current study shows that TONSL is indispensable to many tissue-originated CSCs, which further supports the idea that HRR can be a weak point for CSC survival.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the CSC preference for HRR has also been suggested in breast and gastric CSCs [43,44]. We also recently suggested that HRR may be indispensable for colon CSC survival [45]. The current study shows that TONSL is indispensable to many tissue-originated CSCs, which further supports the idea that HRR can be a weak point for CSC survival.…”
Section: Discussionsupporting
confidence: 83%